Evolutionary studies in the genus Cucumis - Dane, Fennechiena Kloen, author; Workman, Milton, advisor; Lueker, David L., committee member; Bamburg, James R., committee member; Adams, Robert P., committee member; Tsuchiya, T., committee member (Colorado State University. Libraries, 1976)
The evolution of the wild and cultivated Cucumis species was studied by the analysis and comparison of (1) their morphological characteristics, (2) their self-compatibility and intra- and interspecific cross-compatibility levels, (3) their basic chromosome number and meiotic chromosome behavior and that of their interspecific hybrids, (4) the variation, inheritance and geographical distribution of their electrophoretically detectable peroxidase isozymes, (5) their glutamate oxaloacetate transaminase isozyme patterns obtained after polyacrylamide gel electrophoresis, and (6) their peroxidase and esterase banding patterns obtained after isoelectric focusing. Immunological studies with antiserum to C. sativus peroxidases were used to determine the identity, partial or non-identity of the antigenic determinant sites of the Cucumis peroxidases. The genus can be divided into a group of cross-compatible species, distributed over South, East and West Africa, and a group of cross-incompatible species, which includes the two economically important species, C. melo and C. sativus, and three South African species. Ass species except C. sativus (x=7) have a basic chromosome number of x=12. The cross-compatible group of species contains two allotetraploid, one autotetraploid and one hexaploid species, all of which are perennial, five annual diploid (including C. anguria) and two perennial diploid species. Meiotic chromosome studies of interspecific hybrids indicated that the diploid and polyploid species have one genome in common and that the hexaploid has two genomes in common with one allotetraploid species. Allotetraploidy was not accompanied by an increase in the number of multiporate (4) pollen, but autotetraploidy and hexaploidy was. The annual species have the strongest cross-incompatibility barriers, the polyploid species, with the exception of the autotetraploid, the weakest. Chromasomal rearrangements have exerted an influence on the evolution of the Cucumis species since one interspecific hybrid was heterozygous for a translocation and others had a reduction in bivalent chromosome configurations or pollen fertility. Most species displayed a homozygous peroxidase band ing pattern, characterized by peroxidases at one to three genetic loci (Px1, Px2 and Px3 ). Genetic polymorphism was observed at the Px2 locus in four species and at the Px3 locus in two species. The variant peroxidase alleles were codominantly inherited. Geographic variation in the Px2 alleles of C. melo, each represented by a cluster of three bands, could not be correlated with variation in morphological characters and may have been the result of inbreeding or differential selection pressures. An increase in ploidy level had little or no effect on the activity or electrophoretic mobility of the isozymes. South Africa can be considered as the primary gene center of the genus. Only species from the successful cross-compatible group moved northward to establish secondary gene centers. The phylogenetic relationships between the wild species is discussed. C. melo was found to be closer related to three annual South African species (C. africanus, C. leptodermis and C. myriocarpus) than to other Cucumis species. C. sativus was closer related to one annual (C. metuliferus) and one perennial (C. asper) species than to other Cucumis species.
Covers not scanned.
Keywords: Cucurbitaceae